School Principal Management in Enhancing the Digital Competence of Islamic Religious Education Teachers: A Case Study at MIN 7 and MIN 10 Banda Aceh - Ersalmina Ersalmina; Abubakar Abubakar; Wahyu Khafidah; Muslem Daud (Lembaga Teewan Journal Solutions, 2026)
The sustainability of education in the digital era requires continuous improvement in teachers’ digital competencies supported by effective school leadership. This study aims to examine the management practices of school principals in enhancing the digital competence of Islamic Religious Education (IRE) teachers through a case study at Madrasah Ibtidaiyah Negeri (MIN) 7 and MIN 10 Banda Aceh, Indonesia. A mixed-methods approach with a descriptive design was employed, integrating quantitative and qualitative data. Data were collected through questionnaires and semi-structured interviews involving the principals and all teachers engaged in digital learning at both schools, totaling ten participants. The findings reveal that the principals systematically planned and implemented annual programs to strengthen teachers’ digital competence, including digital skills training, educational seminars, teacher workshops, Digital Teacher Working Group (Kelompok Kerja Guru/KKG) activities, reward systems for outstanding teachers, and expanded access to Information and Communication Technology (ICT) resources. Continuous monitoring and evaluation ensured that these programs were implemented effectively according to the annual plans. However, implementation faced challenges related to limited financial resources and inadequate educational facilities and technological infrastructure. The study highlights the crucial role of school principals in fostering teachers’ digital competence and supporting sustainable digital transformation in Islamic primary education.